2D materials and their heterostructures for photocatalytic water splitting and conversion of CO2 to value chemicals and fuels. (11th March 2021) - Shanker, G Shiva; Biswas, Abhijit; Ogale, Satishchandra
Abstract: The rapidly increasing global energy consumption utilizing conventional polluting fuels has been putting enormous stress on the health of our environment and thereby the long term sustainability of the animal and plant life on our planet. The world clearly needs to move rapidly to the alternative sources of environment-friendly, carbon-neutral, clean and renewable energy. To this end, amongst the promising strategies being pursued, one of the best approaches is to produce hydrogen energy from water by using sunlight, with unlimited available resource of both water and sunlight. Concurrently, there is also an emergent need to control CO2 emissions by reducing them to valuable fuels or chemicals using sunlight. For both these goals, it is essential to have efficient, robust and affordable photocatalysts. The early emphasis on semiconductor photocatalysts along with expensive noble-metals co-catalysts has prevented the speedy advance of this energy technology. Extensive efforts are now being expended on designing high-performance photocatalysts based on emergent functional materials endowed with a fascinating set of physical and chemical properties. Towards this end, two-dimensional (2D) materials and their heterostructures have been attracting significant attention lately as potentially viable candidates owing to their unique, and highly tunable optical and electronics functionalities, which are technically adequate for the efficient hydrogen production and conversion of CO2 to fuels. In this topical review, we address the recent progress made in the domain. We believe that by virtue of the uniquely distinct characteristics of their electronic density of states, surface states, high surface area, and diverse possibilities of innovative surface chemical engineering, the 2D materials hold a great promise for facilitating economically viable renewable/clean energy harvesting solution(s) on commercial-scale, thereby accomplishing the urgent task of ensuring the future energy security for the world.